College Enquiry Chatbot System - Amin, Nishmi; Singh, Sweety; Walavalkar, Ashwini (Indian Journal of Computer Science, 2022)
At the time of the admission process students and parents have a lot of questions in their minds for which they either call the administration or have to go to the college which may be miles away from them. Again, it would not be possible for one person to answer 500 calls at a time. The best solution to this problem is a Chatbot that answers all the questions. This project is based on developing a Chatbot that would be a saviour for the college staff at the time of admissions, upcoming exam details, date of release of the result etc.